Effects of a small-sided games training program in youth male soccer players: variations of the locomotor profile while interacting with baseline level and with the accumulated load - Ana Filipa Silva; Rafael Oliveira; Halil Ibrahim Ceylan; Zeki Akyildiz; Francisco Tomás González-Fernández; Hadi Nobari; Mehmet Yıldız; Sabri Birlik; Filipe Manuel Clemente (BMC, 2022)
Abstract Purpose This study aimed to (1) analyze the impact of a small-sided game training program in the locomotor profile of youth male soccer players (while interacting with the baseline level - higher and lower level); and (2) test the relationships between variation in locomotor profile and the accumulated demands in 3v3, 5v5 and match over the period of observation. Methods The cohort lasted 3-weeks. Twenty under-17 male amateur soccer players (16.8 ± 0.41 years; experience: 6.35 ± 0.67 years) were assessed twice for their final velocity at 30−15 intermittent fitness test (VIFT), peak speed at 30-m sprint test (PSS) and anaerobic speed reserve (ASR). The PSS was estimated using a Global Positioning System, while the VIFT was estimated using the maximum level attained by the players during the test. Based on the baseline levels, the scores were standardized using the Z-score. The total score of athleticism (TSA) was calculated per player to organize the players into two groups: lower TSA and higher TSA. Over the three weeks of observation, the small-sided games of 3v3 and 5v5 and match demands were monitored using polar team pro. The heart rate responses (mean and peak), distance covered (overall and split by speed thresholds), and peak speed in these games were obtained and summed over the weeks. The repeated measures ANCOVA tested the variations (time) of the locomotor profile of players while considering the baseline as covariable and the group as a factor. The Pearson-product correlation test analyzed the relationships between variations in locomotor profile (Δ, post-baseline) and the accumulated demands in 3v3, 5v5, and match. Results Between-groups analysis (lower TSA vs. higher TSA) revealed no significant differences on VIFT (p = 0.915), PSS (p = 0.269), ASR (p = 0.258) and TSA score (p = 0.138). Within-group (baseline vs. post-observation) analysis revealed significant difference on VIFT (p < 0.001), PSS (p = 0.008), while no significant differences were found on ASR (p = 0.949) and TSA score (p = 0.619). Significant correlations were found between ΔPSS and match total distance (r = 0.444; p = 0.050), match Z2 (r = 0.481; p = 0.032) and match Z3 (r = 0.454; p = 0.044). Significant correlations were found between ΔTSA and match total distance (r = 0.457; p = 0.043), match Z1 (r = 0.451; p = 0.046), match Z2 (r = 0.500; p = 0.025) and match Z3 (r = 0.468; p = 0.037). Conclusion Significant improvements were observed after the period of observation. However, the fitness baseline level and the accumulated training load in the small-sided games seem to have no significant impact on the observed improvements.